Risk factor management in a contemporary Australian population at increased cardiovascular disease risk - Campbell, D.; Coller, J.; Gong, F.; McGrady, M.; Prior, D.; Boffa, U.; Shiel, L.; Liew, D.; Wolfe, R.; Owen, A.; Krum, H.; Reid, Christopher (Blackwell Publishing, 2018)
Background: Effective management of cardiovascular and chronic kidney disease risk factors offers longer, healthier lives and savings in healthcare. Aim: To examine risk factor management in participants of the SCReening Evaluation of the Evolution of New Heart Failure study, a self-selected population at increased cardiovascular disease risk recruited from members of a health insurance fund in Melbourne and Shepparton, Australia. Methods: Inclusion criteria were age = 60 years with one or more self-reported ischaemic or other heart diseases, irregular or rapid heart rhythm, cerebrovascular disease, renal impairment or treatment for hypertension or diabetes for =2 years. Exclusion criteria were known heart failure or cardiac abnormality on echocardiography or other imaging. Medical history, clinical examination, full blood examination and biochemistry (without lipids and glycated haemoglobin (HbA1c)) were performed for 3847 participants on enrolment, and blood pressure, lipids and HbA1c were measured 1–2 years after enrolment for 3203 participants. Results: Despite 99% of 3294 participants with hypertension receiving antihypertensive medication, half had blood pressures >140/90 mmHg. Approximately 77% of participants were overweight or obese, with one third being obese. Additionally, 74% of participants at high cardiovascular disease risk had low-density lipoprotein cholesterol levels =2 mmol/L, one third of diabetic participants had HbA1c >7%, 22% had an estimated glomerular filtration rate < 60 mL/min/1.73m2, and substantial proportions had under-utilisation of antiplatelet therapy and anticoagulation for atrial fibrillation and were physically inactive. Conclusions: This population demonstrated substantial potential to reduce cardiovascular and renal morbidity and mortality and healthcare costs through more effective management of modifiable risk factors.